Phase transformations of vanadium recovery from refractory stone coal by novel NaOH molten roasting and water leaching technology. Issue 59 (26th July 2017) - Cai, Zhenlei; Zhang, Yimin
Abstract : Phase transformations of vanadium-containing muscovite from refractory stone coal was revealed during novel NaOH molten roasting and water leaching process. Abstract : In this study, a novel NaOH molten roasting and water leaching technology, an eco-friendly process with good selectivity and good availability, was investigated for vanadium recovery from refractory stone coal. In addition, the phase transformations during the vanadium recovery process were also studied. During the NaOH molten roasting process, the monoclinic crystalline structure of muscovite (K(Al, V)2 [Si3 AlO10 ](OH)2 ) was converted into the orthorhombic crystalline structure of Na2 SiO3 and the tetragonal crystalline structure of gehlenite (Ca2 Al2 SiO7 ); this could promote the liberation and recovery of vanadium. During the water leaching process, the tetragonal crystalline structure of gehlenite (Ca2 Al2 SiO7 ) was converted into the monoclinic crystalline structure of Ca3 Si2 O7 ·H2 O. Ca3 Si2 O7 ·H2 O, a kind of C–S–H gel, produced during the water leaching process probably covered the surface of the roscoelite and thus prevented effective vanadium recovery from roscoelite.